Effectiveness of Non-pharmaceutical Interventions in Nine Fields of Activity to Decrease SARS-CoV-2 Transmission - Gómez-Ullate, David; Barbeito, Inés; Precioso, Daniel; Sierra, María José; Vegas Azcárate, Susana; Fernández Balbuena, Sonia; Vitoriano, Begoña; Cao, Ricardo; Monge, Susana (Frontiers, 2023)
Background: We estimated the association between the level of restriction in nine different fields of activity and SARS-CoV-2 transmissibility in Spain, from 15 September 2020 to 9 May 2021. Methods: A stringency index (0-1) was created for each Spanish province (n = 50) daily. A hierarchical multiplicative model was fitted. The median of coefficients across provinces (95% bootstrap confidence intervals) quantified the effect of increasing one standard deviation in the stringency index over the logarithmic return of the weekly percentage variation of the 7-days SARS-CoV-2 cumulative incidence, lagged 12 days. Results: Overall, increasing restrictions reduced SARS-CoV-2 transmission by 22% (RR = 0.78; one-sided 95%CI: 0, 0.82) in 1 week, with highest effects for culture and leisure 14% (0.86; 0, 0.98), social distancing 13% (0.87; 0, 0.95), indoor restaurants 10% (0.90; 0, 0.95) and indoor sports 6% (0.94; 0, 0.98). In a reduced model with seven fields, culture and leisure no longer had a significant effect while ceremonies decreased transmission by 5% (0.95; 0, 0.96). Models R 2 was around 70%. Conclusion: Increased restrictions decreased COVID-19 transmission. Limitations include remaining collinearity between fields, and somewhat artificial quantification of qualitative restrictions, so the exact attribution of the effect to specific areas must be done with caution.
Keywords: COVID-19; SARS-CoV-2; Effectiveness; Hierarchical models; Logarithmic return; Non-pharmaceutical interventions (NPI); Pandemic; Stringency index